A protocol for the management of adhesive small bowel obstruction. Issue 1 (January 2015) - Loftus, Tyler; Moore, Frederick; VanZant, Erin; Bala, Trina; Brakenridge, Scott; Croft, Chasen; Lottenberg, Lawrence; Richards, Winston; Mozingo, David; Atteberry, Linda; Mohr, Alicia; Jordan, Janeen
<x xml:space="preserve">Abstract</x> BACKGROUND Differentiating between partial adhesive small bowel obstruction (aSBO) likely to resolve with medical management and complete obstruction requiring operative intervention remains elusive. We implemented a standardized protocol for the management of aSBO and reviewed our experience retrospectively. METHODS Patients with symptoms of aSBO were admitted for intravenous fluid resuscitation, bowel rest, nasogastric tube decompression, and abdominal examinations every 4 hours. Laboratory values and a computed tomography scan of the abdomen and pelvis with intravenous contrast were obtained. Patients with peritonitis or computed tomography scan findings suggesting bowel compromise were taken to the operating room for exploration following resuscitation. All other patients received 80 mL of Gastroview (GV) and 40 mL of sterile water via nasogastric tube. Abdominal plain films were obtained at 4, 8, 12, and 24 hours. If contrast did not reach the colon within 24 hours, then operative intervention was performed. RESULTS Over 1 year, 91 patients were admitted with aSBO. Sixty-three patients received GV, of whom 51% underwent surgery. Twenty-four patients went directly to the operating room because of clinical or imaging findings suggesting bowel ischemia. Average time to surgery was within 1 day for the no-GV group and 2 days for the GV group. Patients passing GV to the colon within 5 hours of administration had a 90% rate of resolution of obstruction. There was a direct relationship between the duration of time before passing GV to the colon and hospital length of stay (HLOS) (r2 = 0.459). Patients who received GV and did not require surgery had lower HLOS (3 days vs. 11 days, p < 0.0001). CONCLUSION The GV protocol facilitated early recognition of complete obstruction. Administration of GV had diagnostic and therapeutic value and did not increase HLOS, morbidity, or mortality. LEVEL OF EVIDENCE Therapeutic study, level V. Epidemiologic study, level V.